An update on the prevalence and management of Bertolotti's syndrome - Rakauskas, Taylor R.; Gallup, Shannon; Mohamed, Ali A.; Nasice, Jude; Westerhaus, Benjamin (Frontiers in Surgery, 2024)
Bertolotti's Syndrome, a subset of lumbosacral transitional vertebrae (LSTV), is one cause of chronic low back pain (LBP), and a commonly overlooked differential diagnosis. The incidence of Bertolotti's Syndrome has been underestimated in the past and is common in those of younger ages around 30–40. Although diagnostics, imaging methods, and treatment algorithms have been improved in the past few years, there is no gold standard and more long-term, prospective research is needed. The purpose of this mini-review is to increase awareness of Bertolotti's Syndrome, discuss recent advancements in treatment algorithms, and highlight current gaps in the literature.